2019
DOI: 10.21776/ub.apmba.2019.008.01.1
|View full text |Cite
|
Sign up to set email alerts
|

Can Small and Medium Enterprises Survive in MEA 2025: A Case Study of Agro-industry SMEs in Indonesia

Abstract: Food processing agro-industry is a creative industry which immensely contributes to economic development, employment, and Gross Domestic Product (GDP) in Indonesia. Competitiveness is a combination of successful inside and outside of Small Medium Enterprise. Thus, this research aims to 1) get an overview related to the SME food sector and its competitiveness, and 2) understand the influence of entrepreneurial marketing and government policy to Tempe (soybean-cake) chips SME's competitiveness by using Structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…One study revealed that early information sharing significantly lowered perceived risk and enhanced assessments of agency performance (Elisa et al, 2022). Another study found that perceptions of personal in business and government, and the belief that technology concerns could be managed all had a substantial impact on concern (Haryati et al, 2019). Renaldi & Pradana (2023) believe that disclosing ambiguity in risk estimations could cause dispute or confusion among the public rather than resolve it.…”
Section: Risk Perception and Trustmentioning
confidence: 99%
“…One study revealed that early information sharing significantly lowered perceived risk and enhanced assessments of agency performance (Elisa et al, 2022). Another study found that perceptions of personal in business and government, and the belief that technology concerns could be managed all had a substantial impact on concern (Haryati et al, 2019). Renaldi & Pradana (2023) believe that disclosing ambiguity in risk estimations could cause dispute or confusion among the public rather than resolve it.…”
Section: Risk Perception and Trustmentioning
confidence: 99%
“…Entrepreneurship or entrepreneurial orientation has a relation to performance (Haryati et al, 2018;Haryati et al, 2019). Entrepreneurial Orientation (EO) is often mentioned as an antecedent of growth, competitive advantage, and superior performance, and prior empirical research has often shown a positive relationship between EO and performance appears to exist.…”
Section: Variable Of Research Can Be Seen Inmentioning
confidence: 99%
“…Research about marketing and entrepreneurial orientation has already implemented in small business (Haryati et al, 2018) (Haryati, Lilavalicakul, & Surrahman, 2019). Marketing orientation has significant influence to business performance (Ngai, Jimmy, & Ellis, 1998).…”
Section: Introductionmentioning
confidence: 99%